PENGEMBANGAN VIDEO ANIMASI PEMBELAJARAN UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI SISWA PADA MATERI FAKTOR DAN KELIPATAN DI KELAS V SD - Nanda Ika Saputri; Bagus Ardi Saputro; Mei Fita Asri Untari (STKIP Subang, 2025)
This study is motivated by the low literacy and numeracy skills of students on the topic of factors and multiples in fifth grade, and the lack of appropriate learning media. The research problems are the development and effectiveness of an animated learning video to improve these skills. The research method used is Research and Development (R&D) with a one-group pretest-posttest design. The sample consists of 28 fifth-grade students selected using purposive sampling. The results show that the developed animated learning video has a very good validity level. Material expert validation obtained a percentage of 95% (very valid) and media expert validation obtained 98% (very valid). Field trial results showed a positive user response, with a teacher response questionnaire achieving 100% and a student response questionnaire achieving 94.28% (very good). Furthermore, the effectiveness test showed a significant increase in students' numeracy literacy skills. The average pretest score was 50.5 and posttest was 88.5, with an average N-Gain Score of 0.76, which is in the